Equine-assisted services for individuals with substance use disorders: a scoping review - Liam Diaz; Mirinda Ann Gormley; Ashley Coleman; Abby Sepanski; Heather Corley; Angelica Perez; Alain H. Litwin (Substance Abuse Treatment, Prevention, and Policy, 2022)
Abstract The implementation of equine-assisted services (EAS) during treatment for psychological disorders has been frequently documented; however, little is known about the effect of EAS on outcomes for populations with substance use disorder (SUD). The purpose of this scoping review was to synthesize existing literature reporting the effects of EAS when incorporated into SUD treatment. This review followed guidelines in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist for scoping reviews. A search of four databases (MEDLINE/PubMed, PsycINFO, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Academic OneFile) identified studies reporting quantitative and/or qualitative data for an EAS intervention that was implemented among a population receiving treatment for and/or diagnosed with SUD. Of 188 titles, 71 underwent full-text assessment and six met inclusion criteria. Three additional articles were identified through other sources. Quantitative data suggested a potential positive effect of EAS on SUD treatment retention and completion as well as participants’ mental health; however, studies were limited by small sample sizes. Qualitative data indicated that in addition to participants developing bonds with the horses and perceiving EAS as welcomed breaks from traditional treatment, they experienced increased self-efficacy, positive emotional affect, and SUD treatment motivation. Due to methodological limitations and an overall dearth of available studies, the effectiveness of EAS as adjuncts to SUD treatment is inconclusive. Additional research is necessary before supporting broad implementation of EAS as adjuncts to SUD treatment.